Tsunami science and engineering - Heller, Valentin (MDPI AG, 2016)
In 2013, I was approached by the editorial team of the Journal of Marine Science and Engineering to act as guest editor of a Special Issue on tsunamis. I was very keen to take on this project given that recent tragic events such as the 2004 Indian Ocean Tsunami and the 2011 Tōhoku Tsunami had triggered an increase in research activity in this field. The high interest in this Special Issue Tsunami Science and Engineering was reflected by the submission of 21 full length articles. A total of 12 articles were published from 2014 to early 2016 after the rigorous peer-review. This book comprises all 12 contributions to this Special Issue. The overall aim of this collection is to mitigate the destruction of tsunamis and the negative effects they have on us and our environment. The articles cover a wide range of topics around tsunamis and reflect scientific efforts and engineering approaches in this challenging and exciting research field. The first three articles address the generation and propagation phases of tsunamis. Heller and Hager (2014) review the significance of the so-called impulse product parameter P, which is believed to be the most universal parameter for subaerial landslide-tsunami (impulse wave) prediction, and they show how this semi-empirical parameter may be instrumental for preliminary hazard assessment Evers and Hager (2015) show with subaerial landslides impacting a water body that mesh-packed slides result in similar large impulse waves as free granular material. This is very beneficial for a number of reasons including simpler experimental handling. Koyama et al. (2015) describe the difference of the earthquake activity in megathrust subduction zones around Japan, depending on whether an along-dip double segmentation or an along-strike single segmentation is encountered. They further show that earthquakes generated by the latter type result on average in twice as large tsunamis as earthquakes generated by an alongdip double segmentation, after identical seismic moments. The interactions of tsunamis with the shore region and structures are addressed in the following three articles. Barberopoulou et al. (2015) show with historical nautical charts and digital elevation models how dredging, expansion of land and the creation of jetties modified the San Diego harbor over the last 150 years and show how these modifications may change the tsunami amplitudes and current speeds based on different tsunami scenarios. Drähne et al. (2016) address long wave dynamics on coasts and during on-land propagation, based on physical model tests in a novel wave facility with numerical simulations. The authors further successfully compare some of the findings with established analytical expressions. Bremm et al. (2015) investigate the time-history of forces on vertical free-surface-piercing structures exposed to long leading depression waves. The authors characterize and describe in detail the flow patterns during both wave run-up and draw-down and compare the measured total base force with analytically calculated values. Two interesting tsunami hazard assessment approaches are then presented. Anita et al. (2015) propose a comprehensive and total probabilistic approach, in which many different potential source types concur (seismic events, slides, volcanic eruptions, asteroids, etc.), to define a total tsunami hazard. The authors apply this approach to two target sites namely the city of Naples and the island of Ischia in Italy. Alberico et al. (2015) present a GIS-aided procedure using the Papathoma Tsunami Vulnerability Assessment model of urban environments and use Naples as the target site to illustrate the method. A map shows the vulnerability status of Naples and reveals that approximately 21% of the area shows a very high tsunami vulnerability. Two potential past tsunamis are addressed next. McCloskey et al. (2015) present evidence for the occurrence of a large localized tsunami in the Bay of La Paz, approximately 1100 years ago, based on a field study and core data. The authors suggest that the potential tsunami was triggered by the slumping of an island at the eastern edge of the bay and that the tsunami reached up to 3.6 m above mean water. Abril and Periáñez (2015) aimed at quantitatively assessing the potential role of tsunamis in the parting of the Mediterranean Sea in the context of the narrative of the Biblical Exodus, as previously suggested in a number of studies. The authors numerically model several “best case” scenarios and conclude that it is very unlikely that the investigated tsunamis were the potential cause of the parting of the sea. The book finishes with two interesting articles showing that seismic tsunamis may affect the Earth's thermosphere hundreds of kilometers above sea level. Ma et al. (2015) solve generalized ion momentum and continuity equations and investigate how seismic tsunamis create an ionospheric dynamo electric field on the electron density and total electron content perturbations at an altitude of 150 - 600 km. The authors then apply the solution to two arbitrarily selected locations. Ma (2016) conducts similar theoretical work and describes how seismic tsunami excited gravity waves may modulate the atmospheric non-isothermality and wind shears. These brief summaries show the wide range of fascinating topics which are covered in this book. I hope that these articles contribute to the mitigation of the negative effects of tsunamis and inspire many future research activities in this important research field